Do closed waste containers lead to less air contamination than opened? A clinical case study at Jena University Hospital, Germany. (December 2021) - Büchner, Franziskus; Hoffman, Marc; Dobermann, Ute-Helke; Edel, Birgit; Lehmann, Thomas; Kipp, Frank
Highlights: Waste containers source for release of microorganisms into ambient air. Closed waste containers show lowest microbial air contamination. Microbial counts in line with reference limits. Detection of Aspergillus fumigatus in air samples. Abstract: Nosocomial infections are a growing challenge at hospitals. This clinical study aimed to investigate the influence of waste container construction ((open (O), closed (C), and hands-free opening (HF)) on microbial air contamination in a hospital setting. The results are intended to help develop guidelines for waste containers for the collection of non-infectious waste at hospitals and medical facilities. The clinical experiment was conducted at the University Hospital Jena, Germany. Air Impactor samples were performed and microbiologically evaluated for bacteria and fungi both quantitatively and qualitatively. The results were statistically determined using generalized estimating equations. Quantitatively, the lowest bacterial counts in ambient air were found around closed waste containers (114.74 CFU/m 3 ) in comparison to HF (129.28 CFU/m 3 ) and O (126.28 CFU/m 3 ). For fungi, the surrounding air of C (2.08 CFU/m 3 ) and HF (1.97 CFU/m 3 ) waste containers showed a lower impact of fungal air contamination than for O (2.32 CFU/m 3 ). Overall, it was shown that C are more preferable to HF and O waste containers from the point of view of microbial air contamination at hospitals.